Adobe Photoshop CS4 for Photographers - Evening, Martin (Elsevier, 2011)
Martin Evening's Adobe Photoshop for Photographers titles have become classic reference sources for photographers at all skill levels. Whether you are an accomplished user or just starting out, the Adobe Photoshop CS4 for Photographers book contains a wealth of practical advice, hints and tips to help you achieve professional-looking results. Adobe Photoshop CS4 for Photographers begins with an overview of the Photoshop interface and the fundamentals of how to use Photoshop, followed by how to configure and optimize your computer's performance to run the program and then it dives straight into the essentials of Camera Raw image editing. The Sharpening chapter shows how to use the Camera Raw controls to obtain optimum capture sharpening and noise reduction and the Essentials chapter outlines how to work with all the basic image adjustment tools that are in the program, some of which have been there since the very beginning. Practical workshops show you how to master the essential techniques, such as color correction, retouching techniques, toning a black and white image, creating composite images and so on. Each technique is described in step-by-step detail, showing exactly which command to use, whether you are working with a Mac or PC computer. The accompanying DVD contains a Photoshop for Photographers Help Guide. This is supplied in a web browser format that you can either run from the DVD or copy to your computer hard disk for off-line viewing. The Help Guide contains a complete guide to all the tools and panels in Photoshop as well as other items in the program. It is like having an off-line manual with which to learn more about what each Photoshop tool and palette does. The guide also provides 120 minutes of movie tutorials on Photoshop CS4. If you are just beginning to work with digital images or are looking for new ideas, the best techniques and ways to improve the quality of your work, this is the book for you! * Learn Photoshop the Martin Evening way! Get up to speed fast with the essential information you need to create superb images in Photoshop CS4. * Accompnying DVD includes the images you need to follow along as you read, with QuickTime movie tutorials for hands-on learning * Contains over 750 professional, color images